Challenges of the Startup Financing in the Czech Republic - Linhartová, Kateřina; Hnát, Pavel, 1981-; Zeynalov, Ayaz; Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů (2025)
This thesis analyses the financial, and structural factors shaping the Czech startup ecosystem, with a focus on the availability and sources of capital and their impact on innovation-driven growth. Drawing on secondary data on venture capital, international benchmarks, and innovation indicators, the study identifies persistent funding gaps - especially in pre-seed and growth-stage financing - that hinder domestic scaling. To enrich the analysis, twelve semi-structured interviews with founders, investors, and ecosystem experts highlight systemic issues such as limited domestic risk capital, regulatory rigidity, investor distrust in the legal system, cultural risk aversion, and fragmented European markets. Insufficient domestic capital not only constrains firm growth but also contributes to the relocation of startups and talent abroad. The thesis concludes with policy recommendations aimed at strengthening domestic investment capacity, improving legislative conditions, and enhancing the overall competitiveness of the Czech innovation environment.
Vedoucí práce: Pavel Hnát
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů, 2026
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2026
Způsob přístupu: Internet
Keywords: mezinárodní obchod [obor dipl. práce]; diplomové práce; master's theses